Perylene bisimide with diphenylacrylonitrile on side-chain: strongly fluorescent liquid crystal with large pseudo Stokes shift based on AIE and FRET effect. Issue 32 (31st July 2018) - Zhu, Mingguang; Chen, Yunxiang; Zhang, Xiaoyi; Chen, Meihui; Guo, Hongyu; Yang, Fafu
Abstract : A novel perylene bisimide (PBI) derivative with an AIE-active diphenylacrylonitrile unit positioned at the terminal N-imide position through a flexible spacer has been synthesized and characterized. Abstract : A novel perylene bisimide (PBI) derivative with an AIE-active diphenylacrylonitrile unit positioned at the terminal N-imide position through a flexible spacer has been synthesized and characterized. The DSC, POM and XRD studies confirmed that it could self-assemble into a stable hexagonal columnar liquid-crystalline phase between 56 °C and 160 °C. This PBI derivative also exhibited strong fluorescence in solution, thin film and mesophase based on the cooperative mechanism of AIE and FRET between the diphenylacrylonitrile group and perylene moiety. The pseudo Stokes shift was as large as 283 nm, and the fluorescence quantum yields were as high as 0.62–0.79 in solution and 0.68–0.86 in solid state. This study provides a good strategy for converting the columnar liquid crystal with ACQ effect to one with the AIE effect, successfully filling the gap between the excellent columnar mesomorphic properties and strong fluorescence in solid state.